Comparative tactical analysis on the offensive phase between Real Madrid and FCSB football teams - Fratila, I.; Smidu, D.; Smidu, N. (Science, Movement & Health, 2020)
The study aimed to identify the essential aspects regarding the technical-tactical organization on the offensive phase between the Spanish football team Real Madrid and the Romanian football team FCSB, to interpret and compare the differences that are noticed between these two football teams, in order to establish a model that will lead to the optimization of the trainings of the Romanian football teams.The exploratory study involved in the comparative technical-tactical analysis of a top team of Europe and a club team from Romania, started from the premise that the technical-tactical component, represented by behaviors, organization, tactical conception of the game, aspects regarding the collective relations, the forms, the actions that are established between the players, taken as a whole, are defining, essential, determinant in the qualitative evolution, in obtaining the performances, aspects that make the difference between the value level of the football teams. The research methods used are: bibliographic study method, observation method, comparative analysis method, case study method, statistical-mathematical method, video recording method. In order to verify the hypotheses we used the nonparametric Mann-Whitney test (U), setting a significance threshold (p) of 0.05. The values obtained by adding the ranks were introduced in the calculation formulas to determine the values of U1 and U2, and subsequently they were compared with the values in the Mann-Whitney table. The obtained results revealed a significant difference regarding the behavioral organization mode on the offensive phase, aspects revealed both in descriptive and quantitative form. The interpretation of the results in terms of the notes received by the two teams in all the components of the defensive organization phase were rendered with the help of graphs that showed a clear superiority of the Spanish Real Madrid football team over the Romanian FCSB team.